2021
DOI: 10.1016/j.jaccas.2020.11.048
|View full text |Cite
|
Sign up to set email alerts
|

“Be Careful What You Swallow”

Abstract: Swallow (deglutition) syncope is a rare form of neurally mediated cardioinhibitory reflex syncope occurring during swallowing. Patients may present to clinicians across multiple disciplines, so high awareness and careful evaluation are essential. We report 3 such individuals, describing our strategies in diagnosis, investigation and treatment, particularly focusing on conservative management. ( Level of Difficulty: Intermediate. )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…The symptoms of SARS-CoV-2 infection and post-acute sequelae of SARS-CoV-2, or "long COVID," are wide-ranging, but there is emerging evidence of orthostatic intolerance with tachycardia in a number of patients (Dani et al, 2021;Raj et al, 2021;Shouman et al, 2021), and long-COVID-induced postural tachycardia syndrome has been identified by the American Autonomic Society (Raj et al, 2021) as a plausible secondary lingering illness following acute viral recovery from SARS-CoV-2 (Kanjwal et al, 2020;Miglis et al, 2020;Umapathi et al, 2020). COV+ participants in the current study did exhibit greater tachycardia during tilting than CON subjects, though the absolute HR values were not particularly abnormal.…”
Section: Responses To Orthostatic Challengementioning
confidence: 99%
“…The symptoms of SARS-CoV-2 infection and post-acute sequelae of SARS-CoV-2, or "long COVID," are wide-ranging, but there is emerging evidence of orthostatic intolerance with tachycardia in a number of patients (Dani et al, 2021;Raj et al, 2021;Shouman et al, 2021), and long-COVID-induced postural tachycardia syndrome has been identified by the American Autonomic Society (Raj et al, 2021) as a plausible secondary lingering illness following acute viral recovery from SARS-CoV-2 (Kanjwal et al, 2020;Miglis et al, 2020;Umapathi et al, 2020). COV+ participants in the current study did exhibit greater tachycardia during tilting than CON subjects, though the absolute HR values were not particularly abnormal.…”
Section: Responses To Orthostatic Challengementioning
confidence: 99%
“…Swallow syncope is a rare form of cardioinhibitory NMS that occurs when esophageal dilatation during swallowing triggers vagus nerve overstimulation, which leads to sinus arrest and/or transient AV block, resulting in syncope. 1 , 2 Although some investigators have emphasized the importance of lifestyle changes, including avoidance of triggers and diet modification, 2 there seemed to be no apparent triggers for worsening symptoms in the present case. In addition, the patient had already undergone diet modification, avoiding potatoes and carbonated drinks.…”
Section: Discussionmentioning
confidence: 62%
“…It is caused by overactivation of the vagus nerve during swallowing of meals. 1 , 2 Because of the limited efficacy and possible adverse effects of medications and pacemakers, 3 , 4 cardioneuroablation has been proposed as an alternative therapeutic strategy for cardioinhibitory NMS, with promising preliminary results. 5 , 6 , 7 To date, however, there have been only a limited number of case reports on cardioneuroablation for swallow syncope.…”
Section: Introductionmentioning
confidence: 99%
“…Swallow syncope is a rare type of reflex syncope. 1 , 2 Its pathophysiology is probably related to the stimulation of neural pathways that cause vagal hyperactivation generating syncope secondary to a combination of severe bradyarrhythmias and hypotension. 2 Diet modifications and pacemaker implant (when conservative management fails) have been the cornerstones of swallow syncope treatment.…”
Section: Introductionmentioning
confidence: 99%